Representasi Tawakal dalam Lagu “Insha Allah” Karya Maher Zain Berdasarkan Perspektif Al-Ghazali - Amanda Maharani Sandrina; Aria Raizal Muhammad; Shofy Zahwa Syakira; Dadan Firdaus (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Music is one of the effective media for conveying Islamic values, including the concept of tawakal (trust in Allah). Through song lyrics, religious messages can be delivered to listeners in language that is easy to understand while conveying profound meaning. This study aims to analyze the representation of tawakal in the lyrics of Insha Allah by Maher Zain using a semantic approach based on Al-Ghazali’s perspective. This study employed a qualitative approach using the qualitative content analysis method. The research data consisted of selected song lyric excerpts, which were analyzed based on their lexical and contextual meanings and subsequently classified into the three aspects of tawakal according to Al-Ghazali, namely knowledge ('ilm), spiritual state (hal), and action (amal). The findings indicate that the lyrics of Insha Allah represent tawakal through faith in Allah, the transformation of one's inner state from despair to hope, and the act of returning to Allah through prayer and complete surrender. These findings demonstrate that the song functions not only as a form of entertainment but also as a medium for conveying Islamic spiritual values while enriching semantic studies on Islamic song lyrics.